Stakeholder pressure as a driver of risk management practices in public administrations. Issue 1 (24th September 2021) - Schäfer, Fabienne-Sophie; Hirsch, Bernhard; Nitzl, Christian
Abstract : Purpose: Drawing upon new institutional theory and blame avoidance theory, this paper aims to examine how stakeholder pressure has an impact on the implementation and use of risk management practices in public administrations. Furthermore, this paper investigates whether top management support mediates this proposed relationship. Design/methodology/approach: This paper is based on a survey among public financial managers of German municipalities and federal agencies. Data from 136 questionnaires were used to evaluate the model. Findings: The results indicate that top management support fully mediates the relationship between stakeholder pressure and risk management practices. This finding suggests that top management support is crucial for the successful implementation of accounting techniques, such as risk management, in public administrations. Research limitations/implications: This study is based on subjective answers by public financial managers. Moreover, this study is based solely on German data. Hence, future research could use a mixed-method approach and data from other countries. Originality/value: This paper examines whether stakeholder pressure exerts an impact on the sophistication of public risk management practices.